August: Agricultural activities - Sepat, Seema; Kumar, Dinesh (Indian Farming, 2019)
The sowing operations of all kharif crops may have been finished by the end of July. If it has not been done yet due to scanty rainfall or for any other reasons, then ensure sowing in the first week of August, particularly for pulses like blackgram. This year monsoon is delayed, therefore, whatever amount of rainfall is received, it needs to be conserved and utilized properly. Ensuring proper bunds around the field is necessary to capture the rainwater in the field. In case of excess water in all crops except rice, proper arrangements for drainage need to be made. Weed removal is required for better vigour of crops. Infestation of insect-pests should be monitored regularly.